Plant therapy in Africa: Immunostimulatory activity of cell wall polysaccharides - (:unkn) unknown (My University, 2010)
This review article aims to draw attention to therapeutic potential of plant cell wall polysaccharides isolated from African medicinal plants. Plant cell wall, or plant cell extracellular compartment, consists on various polysaccharides having different chemical structures. Among these polysaccharides, cellulose, hemicelluloses and pectin polysaccharides are the predominant ones, and play an important role in controlling several biological processes like cell growth and morphogenesis, or defense mechanisms. The structure-function relationship of plant cell wall polysaccharides have been extensively studied, regarding their in vivo biological functions. Here, we have partially described the chemical structure of several biologically active hemicelluloses or pectin polysaccharides extracts, isolated from different African medicinal plants. It appears that these polysaccharides taken individually are able to modulate the activity of the mammal immune system in different manner, providing an interesting complementary therapy to immune deficient patients for instance. Further investigations on cell wall polysaccharide structure-biological activity relationship of the numerous unexplored medicinal plants are therefore strongly suggested.
Keywords: African Research